Design Improvement Study on a Mobile Rugby Ball Launcher Robot for Indoor Training Purpose - Baharin, Anas; Siti Hana Nasir; Amirul Syafiq Sadun (Progress in Engineering Application and Technology, 2022)
The main focus of previous project is to construct the hardware and software of Semi-Automated Rugby Launcher Robot. Mobile Rugby Launcher Robot were designed for a primary school kid as a first introduction to a rugby sport game. In term of operation system, it allows MR Launcher become more reliable and efficient with this fully-automated controlled process. The previous research simulates how it can be controlled by using remote control system due to features applied in MR Launcher. As to continue the research made, there are several rooms detected as for the improvement which is the storage are still needed due to increase the usefulness and benefits to society. The lack of storage is affecting the time dilation in order to pick and pass the ball. Other than that, based on the existing rugby ball launcher there are no specific storage mechanism that are built in them. Due to the oval-shaped ball, it is difficult to design a structure of the storage and identified the appropriate mechanism improvement needed. Thus, this project propose design for the storage mechanism in MR Launcher which combined with an automatic ball feeder mechanism with high accuracy and precise as to reduce time dilation of the process control.